Early cardiac electrographic and molecular remodeling in a model of status epilepticus and acquired epilepsy. (24th August 2016) - Brewster, Amy L.; Marzec, Kyle; Hairston, Alexandria; Ho, Marvin; Anderson, Anne E.; Lai, Yi‐Chen
Summary: Objectives: A myriad of acute and chronic cardiac alterations are associated with status epilepticus (SE) including increased sympathetic tone, rhythm and ventricular repolarization disturbances. Despite these observations, the molecular processes underlying SE‐associated myocardial remodeling remain to be identified. Here we determined early SE‐associated myocardial electrical and molecular alterations using a model of SE and acquired epilepsy. Methods: We performed electrocardiography (ECG) assessments in rats beginning at 2 weeks following kainate‐induced SE, and calculated short‐term variability (STV) of the corrected QT intervals (QTc) as a marker of ventricular stability. Using western blotting, we quantified myocardial β1‐adrenergic receptors (β1‐AR) and ventricular gap junction protein connexin 43 (Cx43) levels as makers of increased sympathetic tone. We determined the activation status of three kinases associated with sympathetic stimulation and their downstream ion channel targets: extracellular signal‐regulated kinase (ERK), protein kinase A (PKA), Ca 2+ /calmodulin‐dependent protein kinase II (CamKII), hyperpolarization‐activated cyclic nucleotide‐gated channel subunit 2 (HCN2), and voltage‐gated potassium channels 4.2 (Kv4.2 ). We investigated whether SE was associated with altered Ca 2+ homeostasis by determining select Ca 2+ ‐handling protein levels using western blotting. Results: Compared with the sham group, SE animals exhibited higher heart rate, longer QTc interval, and higher STV beginning at 2 weeks following SE. Concurrently, the myocardium of SE rats showed lower β1‐AR and higher Cx43 protein levels, higher levels of phosphorylated ERK, PKA, and CamKII along with decreased HCN2 and Kv4.2 channel levels. In addition, the SE rats had altered proteins levels of Ca 2+ ‐handling proteins, with decreased Na + /Ca 2+ exchanger‐1 and increased calreticulin. Significance: SE triggers early molecular alterations in the myocardium consistent with increased sympathetic tone and altered Ca 2+ homeostasis. These changes, coupled with early and persistent ECG abnormalities, suggest that the observed molecular alterations may contribute to SE‐associated cardiac remodeling. Additional mechanistic studies are needed to determine potential causal roles.